(untitled) (Journal of actual problems of jurisprudence, 2019)
As a result of research of features of bankruptcy, the author has developed the offers, concerning problems of legal regulation in sphere of application of the legislation on bankruptcy. Differences of bankruptcy from bankruptcy of other participants of the civil circulation are revealed, it is offered to recognise «insolvency» as an «inconsistency